2007
DOI: 10.1159/000107662
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phosphodiesterase Type 4 Decreases Stress-Induced Defecation in Rats and Mice

Abstract: Background/Aims: Phosphodiesterase type 4 (PDE4) has been previously shown to regulate colonic contractile activity in vitro. In this study, the effects of PDE4 inhibition were assessed in a model of stress-induced defecation previously demonstrated to be due to increased colonic transit/evacuation. Methods: Rats were individually placed in a mild restraint cage and placed into a 12°C environment (cold-restraint stress) for 60 min. Mice received restraint (only) stress at room temperature for 30 min. Loperamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 70 publications
2
18
0
1
Order By: Relevance
“…Therefore, confirmation that a selective PDE4 activator or a selective A 2B AR agonist can inhibit the ameliorating effect of aminophylline is warranted. Furthermore, these results are consistent with those of previous reports showing that A 2B AR-knockout mice have decreased stool frequency32 and that inhibition of PDE4 suppresses stress-induced defecation35. Nevertheless, they do not agree with the finding by Antonioli et al .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, confirmation that a selective PDE4 activator or a selective A 2B AR agonist can inhibit the ameliorating effect of aminophylline is warranted. Furthermore, these results are consistent with those of previous reports showing that A 2B AR-knockout mice have decreased stool frequency32 and that inhibition of PDE4 suppresses stress-induced defecation35. Nevertheless, they do not agree with the finding by Antonioli et al .…”
Section: Discussionsupporting
confidence: 80%
“…Further, activation of A 1 ARs in the spinal cord has an analgesic effect34. On the other hand, it has been reported that inhibition of PDE4 suppresses stress-induced defecation35. These results suggest that aminophylline (theophylline) may affect visceral hypersensitivity and stress-induced defecation in IBS-D patients and animal models either positively or negatively; however, no study to date has investigated these effects.…”
mentioning
confidence: 99%
“…Although somewhat surprising, we found similar results in BALB/c mice following social defeat stress (Savignac and Cryan, unpublished). The opposite effect was expected, as exposure to a novel environment increases fecal output (Barone et al, 2008; Wang et al, 2010). These data suggest mice may have displayed a decrease in colonic motility which would be relevant to IBS patients displaying a constipation phenotype, which has not been established in traditional IBS mouse models (Bercik et al, 2004; Kimball et al, 2005; Coates et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The apparatus was a gray plastic open arena without any bedding (40 cm × 30 cm × 25 cm, L  ×  W  ×  H ). Mice were allowed 10-min free exploration in the box, behavior was recorded using a video camera and the number of fecal pellets in the arena was counted as an index of anxiety (Barone et al, 2008). For data analysis, the arena was divided into 16 equal areas with the 4 central ones constituting the central zone.…”
Section: Methodsmentioning
confidence: 99%
“…Roflumilast, another example, shows anti-inflammatory and anti-modulatory effects in the pulmonary system by selectively inhibiting phosphodiesterase-4. 76 Amino acid–drug binding data retrieved from PDB show the binding between cAMP-specific 3',5'-cyclic phosphodiesterase 4D (PDE4D) and Roflumilast. Our paralogs survey shows that paralogs PDE4A, PDE4B and PDE4C are potential alternative target proteins.…”
Section: Resultsmentioning
confidence: 99%